The Lutheran Confessions and Popular Religiosity in Latin America - Rieth, Ricardo (Dialog, 2006)
The early history of European missions in Latin America led to a close identity between Confessional Lutheranism and German culture. Following World War II that connection has been all but broken, and Lutherans now swim in the sea of Latin American pluralism, including popular religiosity or the people's religion. Constitutive of the latter is devotion to the saints; and the emphasis on “remembering the saints” in Martin Luther and Philip Melanchthon may become valuable resources in contextualization.